Hubungan Waktu Pemberian MP-ASI Dini dengan Kejadian Diare Pada Bayi Usia 0-12 Bulan di Desa Jaddih Kecamatan Socah Kabupaten Bangkalan: The Relationship between Early Complementary Feeding Time and the incidence of diarrhea in infants aged 0-12 months in Jaddih Village, Socah District, Bangkalan Regency - Nikmah, Nurun; Faizeh, Siti (Jurnal Kebidanan Midwiferia, 2017)
The feeding of companion to baby is very influential of diareehea. The reality still many mothers gave early companion food of breast milk to baby under six months. The purpose oh this research to know the age feeding of companion food of breast milk with the diarrhea case to baby of 1-2 months in Jaddih village Socah Bangkalan. The type oh this research is analytic, the design of this research is cross sectional. The pepulation of this research is all of mothers who have baby the old of 0-12 months is 190 og people. The sample of this research using simple random sampling is 129 of people. The independent variable is early feeding of companion food. The dependent of variable is diarrhea case. The colleting methods of the datausing questionnaire.The analyze of this research using coefficient contingency thes is p= 0,05. The result of this research is the most a part of mother gave early companion food of breast milk to baby (87,6%) and the most a part of baby have experience of diarrhea (77,5%). The result of the coefficient contingency test get the value p=0,0001. There are a relationship between the feeding of aerly companion food of breast milk with diarrhea case to baby 0-12 months in Jaddih Village Socah Bangkalan. The conclusion of this research is there relationship between the feeding of early companion food of breast milk with diarrhea case to baby of age 0-12 months.